CRITICAL THINKING SKILLS ENHANCEMENT OF STUDENTS THROUGH INQUIRY LEARNING MODEL LABORATORY BASED ON REFLECTION OF THE LIGHT - Rahmati Rahmati; Yusrizal Yusrizal; M. Hasan (JIPI (Jurnal IPA dan Pembelajaran IPA), 2017)
Abstract. This study aims to determine the use of inquiry-based learning model laboratory to increase critical thinking skills of students of SMP Negeri 6 Banda Aceh on light reflection material. The method used is a quasi-experimental control group design with pre-test and post-test design. The population in this study is in the eighth grade students of SMP Negeri 6 Banda Aceh. The sampling technique used purposive sampling technique. As for the samples in the study were students VIII2 as an experimental class, and the class as a class VIII5 control the number of students in each class of 30 people. Experimental class taught by laboratory-based inquiry learning model, and the control class was taught by conventional learning models. Data collected through the research instrument is test critical thinking skills in essay form. Conclusions are drawn based on the results of data analysis and processing using Microsoft Word Exel, 2013. The results of data analysis showed an average score of critical thinking skills and experimental control group was 27.90% (low) and 42.02% (moderate). This result was also confirmed by the t-test, the average difference in the improvement of critical thinking skills (α = 0.05) obtained t (6.10) t table (2.39). These results indicate a laboratory-based inquiry learning model can significantly improve the students' critical thinking skills compared with conventional learning models in light reflection material.Keywords: Model inquiry, and critical thinking skills